130k views
1 vote
Solve the system of linear equations by elimination. 3x+3=3y and 2x−6y=2

User Alex Bitek
by
5.6k points

2 Answers

4 votes
Put both equation in standard form Ax + By = C
3x - 3y = -3 ← -2×(3x - 3y = -3) → - 6x + 6y = 6
2x - 6y = 2 → now y-terms are opposites 2x - 6y = 2
add -4x = 8
divide by -4 x = -2
plug x value into one of the equations 3(-2) + 3 = 3y and solve
-6 + 3 = 3y
-3 = 3y
-1 = y
Answer: (-2, -1)
User Canine
by
5.7k points
2 votes
3x + 3 = 3y < -- make this 3x - 3y = -3
2x - 6y = 2

multiply by 2 on the first equation
6x - 6y = -6
2x - 6y = 2
subtract them

4x = -8
x = -2


substitute x = -2 into any of the equation
2x - 6y = 2
2(-2) - 6y = 2
-4 - 6y = 2
-6y = 6
y = -1

So the answer is
(-2 , -1)
User Sean Keating
by
5.6k points